A Pictorial Review on Reversible Splenial Lesions - Sahu, Arpita; Sankhe, Shilpa; Mittal, Kartik; Kamath, Namita; PG, Nandakumar; Sahu, Amit (Indian Journal of Radiology and Imaging, 2021)
Splenium of corpus callosum can be involved in a variety of pathologies causing reversible or irreversible damage. Magnetic resonance imaging (MRI) is a useful investigation to evaluate the same. In spite of the differing etiologies implicated, MRI findings can be quite common. We review the reversible causes of diffusion restriction involving the splenium of corpus callosum and highlight the etiopathologic mechanisms implicated in these pathologies. We further discuss these pathologies in entirety with relevant clinical and laboratory findings helping make definitive diagnosis and guiding appropriate management.
Keywords: diffusion restriction; reversible; splenium